2020
DOI: 10.1038/s41467-020-14889-7
|View full text |Cite
|
Sign up to set email alerts
|

Nanobody-enabled monitoring of kappa opioid receptor states

Abstract: Recent studies show that GPCRs rapidly interconvert between multiple states although our ability to interrogate, monitor and visualize them is limited by a relative lack of suitable tools. We previously reported two nanobodies (Nb39 and Nb6) that stabilize distinct ligand-and efficacy-delimited conformations of the kappa opioid receptor. Here, we demonstrate via Xray crystallography a nanobody-targeted allosteric binding site by which Nb6 stabilizes a ligand-dependent inactive state. As Nb39 stabilizes an acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
118
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(120 citation statements)
references
References 61 publications
2
118
0
Order By: Relevance
“…The most plausible explanation for the observed biphasic response could be compounds at high concentrations hitting intracellular receptors, either with a basal pool of internal receptors or with receptors that have been internalized in response to agonist addition. Although further testing of this hypothesis is beyond the scope of this study, it is supported by previous studies showing that large amounts of intracellular GPCRs exist ( Che et al, 2020 ; Stoeber et al, 2018 ).…”
Section: Discussionsupporting
confidence: 74%
“…The most plausible explanation for the observed biphasic response could be compounds at high concentrations hitting intracellular receptors, either with a basal pool of internal receptors or with receptors that have been internalized in response to agonist addition. Although further testing of this hypothesis is beyond the scope of this study, it is supported by previous studies showing that large amounts of intracellular GPCRs exist ( Che et al, 2020 ; Stoeber et al, 2018 ).…”
Section: Discussionsupporting
confidence: 74%
“…Recent studies have shown that the allosteric range of GPCRs is broader than previously anticipated (33). Engineered antibodies can stabilize both active and inactive receptor conformations (33)(34)(35), and the basal state (R n in our model) represents a time-weighted average of conformational sampling. Our results suggest that G proteins can also act to stabilize both active and inactive receptor conformations and cooperate with agonist binding in both a positive and a negative manner.…”
Section: Discussionmentioning
confidence: 88%
“…Although our results indicate that the distal C terminus of Gα s is required for inactive-state 5-HT 7 -G s complexes, further studies are needed to establish the structural mechanism through which G s stabilizes the inactive state of the receptor. It will be interesting to determine whether G s acts in a manner similar to the way in which negative allosteric antibodies stabilize inactive GPCRs (33)(34)(35). Several other GPCRs are thought to interact with G proteins before agonist binding (4-8); therefore, it seems possible that inverse coupling will prove to be a conserved mechanism for regulating the sensitivity and dynamic range of cell signaling.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that homo-dimerization of µ-opioid receptors can be enhanced by certain agonists suggesting that receptor activation may be modulated by dimerization [ 82 ]. Homo-dimers of κ-opioid receptors were confirmed by crystallography [ 20 , 23 ]. Rhodopsin dimers were seen in native membranes by means of atomic force microscopy [ 83 ].…”
Section: Effects Of Clr On Oligomerization Of Gpcrsmentioning
confidence: 99%